MicroRNA-452-5p regulates fibrogenesis via targeting TGF-β/SMAD4 axis in SCN5A-knockdown human cardiac fibroblasts - Iqra Mushtaq; Tsung-Han Hsieh; Yao-Chang Chen; Yu-Hsun Kao; Yi-Jen Chen (iScience, 2024)
Summary: The mutated SCN5A gene encoding defective Nav1.5 protein causes arrhythmic ailments and is associated with enhanced cardiac fibrosis. This study investigated whether SCN5A mutation directly affects cardiac fibroblasts and explored how defective SCN5A relates to cardiac fibrosis. SCN5A knockdown (SCN5AKD) human cardiac fibroblasts (HCF) had higher collagen, α-SMA, and fibronectin expressions. Micro-RNA deep sequencing and qPCR analysis revealed the downregulation of miR-452-5p and bioinformatic analysis divulged maladaptive upregulation of transforming growth factor β (TGF-β) signaling in SCN5AKD HCF. Luciferase reporter assays validated miR-452-5p targets SMAD4 in SCN5AKD HCF. Moreover, miR-452-5p mimic transfection in SCN5AKD HCF or AAV9-mediated miR-452-5p delivery in isoproterenol-induced heart failure (HF) rats, resulted in the attenuation of TGF-β signaling and fibrogenesis. The exogenous miR-452-5p significantly improved the poor cardiac function in HF rats. In conclusion, miR-452-5p regulates cardiac fibrosis progression by targeting the TGF-β/SMAD4 axis under the loss of the SCN5A gene.